Underwater Image Enhancement Using Histogram Method - J. Brindha; V. Vijayakumar (Institute of Advanced Engineering and Science, 2017)
The underwater images not only offer aninteresting sight, but also have a challenge to monitor marinespecies and underwater activities. Taking a beautiful underwater image requires extraordinary equipment and technique. Usually,there are distorted colors on the image caused by poor light andwater quality. So it requires an image enhancement process to geta proper photo to display. This research offers an improvedmethod of auto levels to produce stunning photos. This methoduses the color balancing based on the distribution of each channelR, G and B based on its histogram. The balancing of colors willreproduce colors more attractive compared with other methodsof auto level.